Community-level predictors of Australian children's dental caries and injury - Stormon, N; Ford, P J; Lalloo, R (My University, 2019)
Social determinants of oral health are complex and have been described by conceptual frameworks. A widely embraced model of children's oral health was published by Fisher-Owens et al. (2007), identifying theoretical constructs influencing oral health. The current study aimed to investigate community-level constructs described in the conceptual model. The Longitudinal Study of Australian Children is a cross-sequential dual cohort study, with a representative sample (n = 10090) of Australian children. Generalized estimating equations were applied to model seven waves of carer-reported oral health and community measures. In the final model, children living in Queensland had a 1.48 (CI 1.35-1.62) increased odds of dental caries over time. Children in low socio-economic status (SES) areas (OR 1.32 CI 1.20-1.44) had an increased odds of caries. The state of Queensland (OR 1.24 CI 1.05-1.46) and poor neighbourhood liveability (OR 1.17 CI 1.05-1.31) were predictors of dental injury. By modelling available community measures, this study found SES and rurality were predictors of caries over childhood. Our results highlight the difficulty of applying conceptual models to oral health. The use of qualitative studies and realist reviews should be considered to complement statistical models to provide contextualized insights into funding, policy and service delivery on children's oral health.
Australian Dental Journal
Keywords: Childhood and child development; Health and wellbeing